Women as managers in male dominated companies their leadership style and level of work stress. - Rosero, Cherrylyn Doctolero; Sioson, Marianne Solacito (2004.)
The study sought to determine the leadership style and level of work stress of selected female managers, age 22-63, in male dominated companies. Forty-two (42) female managers in male dominated companies in the cities of Iloilo and Bacolod served as respondents in the study., The Leadership Quationnaire and Work Streaa Profile were utilized for data gathering. Results showed that most female managers' experiences low level of work stress. Moreover, it was found out that the leadership style and level of work stress have no significant relationship from each other, since x squared computed less than x squared.05 critical (3.842>3.315).
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Women